Experimental Investigation on Concrete with Replacement of Cement & Fine Aggregate by Fly Ash & Marble Dust - Kumar Goyal, Pradeep; Kumar, Niraj; Kumar Sharma, Devendra (International Journal of Computer Sciences and Engineering, 2025)
The use of conservative concrete when used in large volume takes more cost as compared to modified concrete using the waste marble dust and fly ash obtained from thermal power plant. Also the strength of concrete using marble dust and fly ash increases up to a certain extent which proves to be more inexpensive. Cement is used in construction and it emits CO₂ in very large amount which damaging environment. As the cement content in concrete going to be decrease so the sustainable development of environment takes place which in turn makes effective in terms of health of people.